2022
DOI: 10.1038/s41598-022-08249-2
|View full text |Cite
|
Sign up to set email alerts
|

The source of the fat significantly affects the results of high-fat diet intervention

Abstract: High-fat diet (HFD) is widely used in animal models of many diseases, it helps to understand the pathogenic mechanism of related diseases. Several dietary fats were commonly used in HFD, such as corn oil, peanut oil, soybean oil, sunflower oil, and lard. However, it was reported that different dietary fat could have completely different effects on physiological indicators and the gut microbiome, and the sources of dietary fat used in high-fat diet research have not been comprehensively compared. In this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 59 publications
0
14
0
3
Order By: Relevance
“…Pork oil has been shown to increase body weight when consumed in large quantities significantly. (30) In this study, all experimental animals given a high-fat diet were obese.…”
Section: Discussionmentioning
confidence: 96%
“…Pork oil has been shown to increase body weight when consumed in large quantities significantly. (30) In this study, all experimental animals given a high-fat diet were obese.…”
Section: Discussionmentioning
confidence: 96%
“…Relmβ is a chemotactic factor for CD4 + T cells, which are critical for C. rodentium clearance (Simmons et al, 2003). Other studies have explored the effect of high‐fat diets in C. rodentium infection with variable results, possibly due to the fact that the effects of diets in the colonic microbiome and immunity are highly dependent on the type and source of the fat (An et al, 2022; DeCoffe et al, 2016; Ghosh et al, 2013; Maattanen et al, 2020) and different types of fats can have opposite effects (Hekmatdoost et al, 2013). A recent study reported that administration of a high‐fat/low fiber diet for 1 week previous to infection with C. rodentium reduced its initial colonization, which was restored to normal levels upon dietary fiber supplementation (An et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A HFD has been found to significantly reduce the diversity of gut microbiota ( Wan et al., 2019 ), resulting in a decrease in the number of bacteria that are responsible for maintaining the integrity of the gut mucosal barrier and an increase in the number of bacteria that breach it ( Monk et al., 2019 ; Zhang et al., 2019a ). This alteration in gut microbiota is characterized by a reduction in the relative abundance of Bacteroides and an increase in the relative abundance of Firmicutes ( An et al., 2022 ). Moreover, the concentration of lipopolysaccharide (LPS) has been found to increase with the number of Actinomycetes while the number of Bifidobacteria declines as Vibrio desulfonate increased.…”
Section: A High-fat Diet Alters Gut Permeability and Gut Microbiota I...mentioning
confidence: 99%